To mesh or not to mesh: a review of pelvic organ reconstructive surgery - Dällenbach P (Dove Medical Press, 2015)
Patrick Dällenbach Department of Gynecology and Obstetrics, Division of Gynecology, Urogynecology Unit, Geneva University Hospitals, Geneva, Switzerland Abstract: Pelvic organ prolapse (POP) is a major health issue with a lifetime risk of undergoing at least one surgical intervention estimated at close to 10%. In the 1990s, the risk of reoperation after primary standard vaginal procedure was estimated to be as high as 30% to 50%. In order to reduce the risk of relapse, gynecological surgeons started to use mesh implants in pelvic organ reconstructive surgery with the emergence of new complications. Recent studies have nevertheless shown that the risk of POP recurrence requiring reoperation is lower than previously estimated, being closer to 10% rather than 30%. The development of mesh surgery – actively promoted by the marketing industry – was tremendous during the past decade, and preceded any studies supporting its benefit for our patients. Randomized trials comparing the use of mesh to native tissue repair in POP surgery have now shown better anatomical but similar functional outcomes, and meshes are associated with more complications, in particular for transvaginal mesh implants. POP is not a life-threatening condition, but a functional problem that impairs quality of life for women. The old adage “primum non nocere” is particularly appropriate when dealing with this condition which requires no treatment when asymptomatic. It is currently admitted that a certain degree of POP is physiological with aging when situated above the landmark of the hymen. Treatment should be individualized and the use of mesh needs to be selective and appropriate. Mesh implants are probably an important tool in pelvic reconstructive surgery, but the ideal implant has yet to be found. The indications for its use still require caution and discernment. This review explores the reasons behind the introduction of mesh augmentation in POP surgery, and aims to clarify the risks, benefits, and the recognized indications for its use. Keywords: pelvic organ prolapse surgery, mesh surgery, review, pelvic floor, mesh implants